Insect tissue-specific vitellogenin facilitates transmission of plant virus - Huo, Yan; Yu, Yuanling; Chen, Liying; Li, Qiong; Zhang, Mengting; Song, Zhiyu; Chen, Xiaoying; Fang, Rongxiang; Zhang, Lili (PLoS pathogens, 2018)
Insect vitellogenin (Vg) has been considered to be synthesized in the fat body. Here, we found that abundant Vg protein is synthesized in Laodelphax striatellus hemocytes as well. We also determined that only the hemocyte-produced Vg binds to Rice stripe virus (RSV) in vivo. Examination of the subunit composition of L. striatellus Vg (LsVg) revealed that LsVg was processed differently after its expression in different tissues. The LsVg subunit able to bind to RSV exist stably only in hemocytes, while fat body-produced LsVg lacks the RSV-interacting subunit. Nymph and male L. striatellus individuals also synthesize Vg but only in hemocytes, and the proteins co-localize with RSV. We observed that knockdown of LsVg transcripts by RNA interference decreased the RSV titer in the hemolymph, and thus interfered with systemic virus infection. Our results reveal the sex-independent expression and tissue-specific processing of LsVg and also unprecedentedly connect the function of this protein in mediating virus transmission to its particular molecular forms existing in tissues previously known as non-Vg producing.